Satisfying Children's Desire: A Primary Value Driving Parents' Food Purchasing Decisions for Elementary-school-aged Children in South Carolina (P10-043-19). (13th June 2019) - Monalisa, Nazratun; Frongillo, Edward; Blake, Christine; Steck, Susan; DiPietro, Robin
Abstract: Objectives: This study aimed to understand how parents made food purchasing decisions for their elementary-school-aged children and how they adjudicated among different values to make a purchasing decision. Methods: Semi-structured qualitative interviews were conducted with 40 parents from low-and middle-income families in South Carolina who were primary food shoppers for their elementary-school-aged children and the households. The interviews were audio-recorded, transcribed verbatim, and open-coded. Coding matrices were used to compare parents' responses on their decision-making process by race/ethnicity and child age. Results: Parents adjudicated among nine values when they purchased foods and drinks for their elementary-school-aged children. Satisfying children's desire for a food or drink was the primary value parents identified as driving their food purchasing decisions. Parents also valued nutritional quality of the foods, children's acceptance of the foods, convenience of preparation, cost, health needs of the children, and tradition. Parents wanted their children to eat healthy but reported that they might need to compromise with the healthfulness of the foods because of their children's desire for less healthy foods. Although parents perceived that healthy foods, including fresh fruits and vegetables, are expensive, they wanted to accommodate those foods in their shopping list regardless of the cost if their children desired those foods. Strategies that parents applied to make a balance between children's desire, healthfulness of the foods, and price of the foods included purchasing store brand items, seasonal fruits, and items on sale and promotion, as well as setting rules for the children. Conclusions: Making food purchasing decision for children is complex as children's desire and acceptance of a food are important in parents' decisions. Despite that parents valued nutritional quality of foods and health needs, they tend to buy less healthy foods to satisfy their children's desire. Funding Sources: This study was partially funded by a SPARC grant from the University of South Carolina Office of the Vice President for Research and the Olga I. Ogoussan Doctoral Research Award from the Department of Health Promotion, Education, and Behavior, Arnold School of Public Health, University of South Carolina.